The Implementation of Payroll Accounting Information Systems In Indonesia: A Systematic Literature Review - Ria; Khairul Saleh L. Tobing; Dhieka Avrilia Lantana; Kumba Digdowiseiso; Nurasyikin Jamaludin (CV ODIS, 2023)
This research presents an in-depth analysis of the implementation of the Payroll Accounting Information System in Indonesia through a Systematic Literature Review (SLR) approach. Involving ten accredited journals, this research describes the processes and obstacles in payroll systems in various companies, including PT. Varia Usaha Bahari, Faculty of Economics and Business, Sam Ratulangi University, and PT. True Primary Gamma. The results show that there are deficiencies in internal control, such as duplication of tasks and lack of efficiency in preparing payroll. Even though several companies have implemented payroll accounting information systems well, there are still weaknesses in supporting documents and internal controls. This research shows that effective implementation of a payroll accounting information system requires good integration between technology, managerial supervision, and a well-organized company organizational structure. Challenges continually arise with the development of technology, requiring companies in Indonesia to continually improve their payroll systems to remain compliant with applicable accounting standards and ensure effective internal controls. This research provides comprehensive insight into developments and trends in this domain, providing a basis for companies to improve their payroll systems to achieve salary management that is accurate, reliable and compliant with applicable regulations.